2016
DOI: 10.36790/epistemus.v10i21.32
|View full text |Cite
|
Sign up to set email alerts
|

Disfruto El Poder De Ser Feliz: Experiencia en Personas Que Viven Con Vih

Abstract: Las personas que viven con virus de inmunodeficiencia humana (VIH) pueden presentar alteraciones biopsicosociales que generan infelicidad. La gaudibilidad (capacidad para ser feliz y disfrutar), puede favorecerse al crear nuevos patrones de conducta mental con la programación neurolingüística (PNL). El propósito fue: analizar la experiencia vivida en un taller de PNL para personas que viven con VIH, a la luz del referente teórico de; Rogers. Estudio cualitativo con diseño fenomenológico, participaron 12 person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Four out of five patients perceived having sufficient total social support, in which the dimensions of confidential support, and affective resources were sufficient in more than half of the participants, coinciding with what was observed by Mosqueda-Ramírez et al, 13 in a cross-sectional study carried out in a capasits, in Tenosique Tabasco, using the same instrument. Regarding sociodemographic factors, it was found that the average age was in their 40's, with a predominance of men living in free union, similar to that reported by Beltrán-De la Rosa et al, 23 however, it differed in terms of sexual preference, and time of diagnosis, which may be related to the characteristics of the population, since it is a young adult population with an active sexual life.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Four out of five patients perceived having sufficient total social support, in which the dimensions of confidential support, and affective resources were sufficient in more than half of the participants, coinciding with what was observed by Mosqueda-Ramírez et al, 13 in a cross-sectional study carried out in a capasits, in Tenosique Tabasco, using the same instrument. Regarding sociodemographic factors, it was found that the average age was in their 40's, with a predominance of men living in free union, similar to that reported by Beltrán-De la Rosa et al, 23 however, it differed in terms of sexual preference, and time of diagnosis, which may be related to the characteristics of the population, since it is a young adult population with an active sexual life.…”
Section: Discussionsupporting
confidence: 82%
“…12 The presence of social support in people living with hiv can provide benefits to the patient, because it facilitates their psychosocial adjustment to the disease, and provides a better quality of life due to the help they receive from their support networks (in the form of family, friends, partners, among others); this leads to better physical, and mental health conditions due to the emotional and material resources they obtain from these relationships. 13 The learning that hiv generated during the covid-19 pandemic should be considered in order to anticipate needs, with respect to the inequity in health caused by the sociodemographic conditions of people suffering from this disease, with the purpose of generating an environment that promotes and guides changes in habits, abate stigmas, and reinforce multidisciplinary work. 14 Given the interrelationship of the above factors, the objective of this research was to determine the prevalence of anxiety and depression, and to identify the social support networks in patients with hiv/aids during the covid-19 pandemic in a second-level hospital.…”
Section: Introductionmentioning
confidence: 99%
“…2024;25(1):12-18. http://dx.doi.org/10.22201/fm.14058871p.2024.187138 1 orna: Odds ratio no ajustado, 2 ic 95%: Intervalo de confianza de 95% de Miettinen. de los participantes, coincidiendo con lo observado por Mosqueda-Ramírez y cols., 13 en un estudio transversal realizado en un capasits de Tenosique Tabasco utilizando el mismo instrumento. Respecto a los factores sociodemográficos se encontró que la edad promedio se ubicó en la cuarta década de la vida, con predominio del sexo masculino y en unión libre, similar a lo reportado por Beltrán-De la Rosa y cols., 23 sin embargo, difirió en cuanto a la preferencia sexual y tiempo de diagnóstico de la enfermedad, lo cual puede estar relacionado con las características de la población, ya que se trata de una población adulta joven y con vida sexual activa.…”
Section: Discussionunclassified
“…12 La presencia de apoyo social en personas que viven con vih puede proporcionar beneficios en el individuo, porque facilita su ajuste psicosocial hacia la enfermedad y otorga una mejor calidad de vida por la ayuda que recibe de sus redes de apoyo (en forma de familia, amigos, pareja, entre otros); esto propicia mejores condiciones de salud física y mental debido a los recursos emocionales y materiales que obtienen de estas relaciones. 13 Se debe considerar el aprendizaje que el vih generó durante la pandemia de la covid-19 con la finalidad de anticipar necesidades, respecto a la inequidad en salud ocasionada por las condiciones sociodemográficas de personas que padecen esta enfermedad, esto con el propósito de generar un ambiente que promueva y guíe cambios de hábitos, abatir estigmas y reforzar el trabajo multidisciplinario. 14 Dada la interrelación de los factores referidos, el objetivo de esta investigación fue determinar la prevalencia de ansiedad y depresión, e identificar las redes de apoyo social en pacientes con vih/sida durante la pandemia por covid-19 en un hospital de segundo nivel.…”
Section: Introductionunclassified